Pemberian Stimulasi Selama Satu Jam pada Perkembangan Anak Usia 12-24 Bulan - Mira Irmawati; I Gusti Ayu Indah Ardani Ayu Indah Ardani; Dewi Astasari; Irwanto Irwanto; Ahmad Suryawan; Moersintowarti B Narendra (MEDIA MEDIKA INDONESIANA, 2012)
The influence of one hour stimulation in children aged 12-24 monthsIntroduction: Early stimulation plays an important role to reach optimal growth and development in children, especially cognitive, affective, and psychomotor developments. Stimulation has to be done continuously because this is important to maintain the connection between brain cells (synapse). Lack of stimulation can influence loss of brain cells functions. The aim of this study is to determine the influence of one hour stimulation on the development of children aged 12-24 months.Methods: An experimental analytic study with cohort prospective was conducted on children aged 12-24 months in Gubeng district, Surabaya, from September 2008-February 2009. Seventy healthy children were randomly divided into two groups, stimulation group and control group. Denver II was used to evaluate children’s developmental status, conducted before and after stimulation. Data analysis using McNemar and Chi Square test.Result: There were improvement on development in both groups, from 85.7% become to 94.3% in the stimulation group and 68.6% to 77.1% in the control group. There was a significant influence on children development, only 10% children did not have any development delay anymore in the stimulation group, but in the control group still 30% (p=0.042). After 3 months, there was an improvement of development in the stimulation group from suspect to normal in 80%, and 63.6% in the control group, but notsignificant (p=0.375 vs p=0.549).Conclusion: Early stimulation improves the development of children aged 12-24 months.Keywords: Children, aged 12-24 months, early stimulation, Denver II ABSTRAKPendahuluan: Stimulasi mempunyai peran penting untuk meningkatkan pertumbuhan dan perkembangan anak, terutama fungsi kognitif, afektif dan psikomotor. Stimulasi yang terus menerus mengakibatkan hubungan antar sel otak (sinapsis) bisa berjalan dengan baik. Kurangnya stimulasi akan mengakibatkan hilangnya fungsi sel-sel otak ini. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian stimulasi selama 1 jam pada perkembangan anak usia 12-24 bulan.Metode: Penelitian dilakukan secara analitik prospektif kohort pada anak usia 12-24 bulan di Kecamatan Gubeng, Surabaya, mulai bulan September 2008 hingga Februari 2009. Tujuh puluh anak sehat secara acak dibagi dalam 2 kelompok, kelompok stimulasi dan kelompok kontrol. Denver II digunakan untuk menilai status perkembangan anak, sebelum dan sesudah perlakuan. Analisis data menggunakan uji McNemar dan Chi Square.Hasil: Didapatkan perbaikan perkembangan pada kedua kelompok, dari 85,7% menjadi 94,3% pada kelompok stimulasi, dan 68,6% menjadi 77,1% pada kelompok kontrol. Terdapat perbedaan bermakna pada kemampuan perkembangan, hanya 10% tidak mengalami keterlambatan pada kelompok stimulasi, sedangkan kelompok kontrol 30% (p=0,042). Setelah 3 bulan, terjadi peningkatan perkembangan pada kelompok stimulasi dari subyek yang suspek menjadi normal sebesar 80%, dan kelompok kontrolsebesar 63,6%, tetapi tidak bermakna (p=0,375 vs p=0,549).Simpulan: Pemberian stimulasi satu jam meningkatkan kemampuan perkembangan anak usia 12-24 bulan.